1984
DOI: 10.1111/j.2044-8279.1984.tb02591.x
|View full text |Cite
|
Sign up to set email alerts
|

The Transferability of Two Pictorial Scientific Tasks Between Different Spatial Dimensions

Abstract: Summary. Students in Cape Verde and Pakistan worked through different versions of two instructional programmes intended to teach the visualisation of reflection or rotation respectively in diagrams of three‐dimensional structures. The three versions of the Reflections Programme were concerned respectively with reflections across a different Cartesian plane; the three versions of the Rotations Programme were concerned respectively with rotations about a different Cartesian axis. The results on a post‐test indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…If, as suggested, perception of pictorial depth and ability to integrate pictures correctly are two independent factors, then this finding is of practical interest since it may be held to elucidate the difficulties of interpretation of geometrical and technical drawings which are reported in the literature (Leach, 1975;Seddon, Einaiyeju & Jusoh, 1984;Seddon, Tariq & Dos Santos Veiga, 1984), and by so doing suggest remedial measures, as, presumably, different measures would be called for in the case of those individuals whose difficulties arise from their inability to perceive pictorial depth, than in the case of those individuals whose difficulties are those of construction of coherent mental models.…”
Section: Discussionmentioning
confidence: 79%
“…If, as suggested, perception of pictorial depth and ability to integrate pictures correctly are two independent factors, then this finding is of practical interest since it may be held to elucidate the difficulties of interpretation of geometrical and technical drawings which are reported in the literature (Leach, 1975;Seddon, Einaiyeju & Jusoh, 1984;Seddon, Tariq & Dos Santos Veiga, 1984), and by so doing suggest remedial measures, as, presumably, different measures would be called for in the case of those individuals whose difficulties arise from their inability to perceive pictorial depth, than in the case of those individuals whose difficulties are those of construction of coherent mental models.…”
Section: Discussionmentioning
confidence: 79%
“…The most sustained efforts at finding an adequate method of teaching the perceptual skills needed to comprehend spatial representations and to perform some of the mental transformations described above were made by teachers of chemistry whose students must use complex diagrams of molecular structures. The findings have been published in a number of papers Mitchelmore 1978;1980a;1980b;Seddon 1985;Seddon, Einaiyeju & Jusho 1984;Seddon, Tariq & Dos Santos Veiga 1984); all show considerable differences in pictorial skills among students drawn from various cultures and suggest that students from some cultures may find it particularly difficult to understand diagrams.…”
Section: A Caveat and Some Practical Implicationsmentioning
confidence: 91%
“…As regards empirical evidence concerning the distinction between the psychological properties of visualising rotations about the X-or Y-axes, on the one hand, and the Z-axis, on the other, successful attempts to teach students to visualise rotations about the Xand Y-axes had no effect on the visualisation of rotation about the Z-axis, and vice versa (Seddon, Tariq and Santos Veiga, 1984). Also, factor analytic studies have always produced a factor for visualising rotations about the Z-axis which is different from those observed for rotations about the X-and Y-axes (Seddon, Tariq and Santos Veiga, 1982; Seddon, Eniaiyeju and Chia, 1985).…”
Section: Rotation Aboutmentioning
confidence: 99%
“…In fact, the empirical evidence reveals different results from different investigations. For example, Seddon, Tariq and Santos Veiga (1984) found that there was no transfer between the ability to visualise rotations about these two axes, when the students were given instruction in visualising rotation about only one. The factor analytic investigations of Seddon, Tariq and Santos Veiga (1982), as well as of Seddon, Eniaiyeju and Chia (1985) variously revealed separate factors for the Xand Y-axes with some samples of students, but a factor common to both axes with others.…”
Section: Rotation Aboutmentioning
confidence: 99%